Quantification of Live Bacterial Sensing for Chemotaxis and Phagocytosis and of Macropinocytosis - Meena, Netra P.; Kimmel, Alan R. (Frontiers in Cellular and Infection Microbiology, 2018)
Initial immunological defense mechanisms to pathogen invasion rely on innate pathways of chemotaxis and phagocytosis, original to ancient phagocytes. Although chemotaxis has been well-studied in mammalian and model systems using purified chemoattractants in defined conditions, directed movement toward live bacteria has been more difficult to assess. Dictyostelium discoideum is a professional phagocyte that chemotaxes toward bacteria during growth-phase in a process to locate nutrient sources. Using Dictyostelium as a model, we have developed a system that is able to quantify chemotaxis to very high sensitivity. Here, Dictyostelium can detect various chemoattractants at concentrations <1 nM. Given this exceedingly sensitive signal response, Dictyostelium will migrate directionally toward live gram positive and gram negative bacteria, in a highly quantifiable manner, and dependent upon bacterially-secreted chemoattractants. Additionally, we have developed a real-time, quantitative assay for phagocytosis of live gram positive and gram negative bacteria. To extend the analyses of endocytic functions, we further modified the system to quantify cellular uptake via macropinocytosis of smaller (<100 kDa) molecules. These various approaches provide novel means to dissect potential for identification of novel chemoattractants and mechanistic factors that are essential for chemotaxis, phagocytosis, and/or macropinocytosis and for more detailed understanding in host-pathogen interactive defenses.